Farewell ceremony to celebrate the indispensable contributions of Dr. Nadiah Zafar and Associate Professor Dr. Aisyah Saad Abdul Rahim / Mohd Alimukhti Mansor, Nik Aisyah Najwa Nik Mustaffa Shapri and Dr. Gurmeet Kaur Surindar Singh - Mansor, Mohd Alimukhti; Nik Mustaffa Shapri, Nik Aisyah Najwa; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
On August 25, 2023, the Welfare and Recreation Club of the Faculty of Pharmacy organised a farewell ceremony for two lecturers, namely Dr. Nadiah Zafar and Associate Professor Dr. Aisyah Saad Abdul Rahim. The event that was held at the Banquet Room, FF2 Building, Faculty of Pharmacy, UiTM Puncak Alam, served as a platform to acknowledge and appreciate their exceptional service and unwavering dedication throughout their tenure at the Faculty of Pharmacy and UiTM. The faculty holds Dr. Nadiah Zafar and Associate Professor Dr. Aisyah Saad Abdul Rahim in the highest regard for their significant contributions and unwavering commitment to education. Their commitment, dedication, and contributions have been indispensable to the growth and success of our esteemed academic community.